2011
DOI: 10.3390/cancers3021744
|View full text |Cite|
|
Sign up to set email alerts
|

Canine Mammary Cancer Stem Cells are Radio- and Chemo- Resistant and Exhibit an Epithelial-Mesenchymal Transition Phenotype

Abstract: Canine mammary carcinoma is the most common cancer among female dogs and is often fatal due to the development of distant metastases. In humans, solid tumors are made up of heterogeneous cell populations, which perform different roles in the tumor economy. A small subset of tumor cells can hold or acquire stem cell characteristics, enabling them to drive tumor growth, recurrence and metastasis. In veterinary medicine, the molecular drivers of canine mammary carcinoma are as yet undefined. Here we report that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 64 publications
5
53
0
Order By: Relevance
“…Hereby, it was found that the CSC were more resistant to the actions of interferon-omega than the REM134 and CAT-MT cell lines [75]. A similar result was found with the chemotherapeutic drug doxorubicin, where spheres derived from the canine adenocarcinoma cell line CHMp and REM134 had chemoresistant characteristics [72,73]. Taken together, it can be stated that such sphere assays are suitable models to test therapeutic strategies aimed at eradicating CSC.…”
Section: Figsupporting
confidence: 62%
See 1 more Smart Citation
“…Hereby, it was found that the CSC were more resistant to the actions of interferon-omega than the REM134 and CAT-MT cell lines [75]. A similar result was found with the chemotherapeutic drug doxorubicin, where spheres derived from the canine adenocarcinoma cell line CHMp and REM134 had chemoresistant characteristics [72,73]. Taken together, it can be stated that such sphere assays are suitable models to test therapeutic strategies aimed at eradicating CSC.…”
Section: Figsupporting
confidence: 62%
“…Moreover, these CD44 + CD24 -populations showed a high ALDH activity and were capable of initiating tumors in NOD/SCD mice [72]. CSC spheres, isolated from REM134, were shown to express the embryonic stem cell markers Oct4 and Nanog as assessed by nonquantitative RT-PCR analysis [73]. The group of Ferletta et al [74] isolated spheres from the mammary tumor cell line CMT-U229 (an atypical benign mixed mammary tumor), characterized these spheres by IHC and found a similar expression pattern to what had been described by other research groups [72,73].…”
Section: Figmentioning
confidence: 99%
“…Recent studies have described plasticity of epithelial cells that undergo the epithelialemesenchymal transition (EMT) that is necessary for the invasion and metastasis of carcinomas (Vincent-Salomon and Thiery, 2003;Huber et al, 2005;Pereira et al, 2010). EMT was originally defined in gastrulation and neural crest delamination during embryonic morphogenetic remodelling (Reiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used this method to analyze the sphere-forming ability of canine mammary CSCs (15,23). This method has also been used to investigate novel therapeutic drugs in humans and canines (14,24).…”
Section: Discussionmentioning
confidence: 99%
“…In canines, mammary CSCs are associated with a higher grade of carcinoma and poor prognosis (7,8). In addition, canine mammary CSCs are typically resistant to common cancer therapies (9,15). Therefore, it is important to identify novel drugs targeting CSCs for the eradication of canine, and human, mammary tumors.…”
Section: Discussionmentioning
confidence: 99%